Nutrient Management on the Water Productivity and Profitability of Hyacinth Bean in Baby Corn (Zea mays L.) - Hyacinth Bean (Lablab purpureus var. typicus) Cropping System - Preetham, R.; Kumar, K. Avil; Srinivas, A.; Rao, A. Manohar; Ramprakash, T. (International Journal of Bio-resource and Stress Management, 2020)
The field experiments were conducted in semi-arid region during rabi seasons of 2015-16 and 2016-17 to study the effect of integrated nutrient management practices on water productivity and profitability of hyacinth in baby corn – hyacinth bean cropping system. Experiment was laid in Randomized Block Design for baby corn during kharif 2015 with seven treatments comprised of 100% recommended dose of fertilizers (RDF 150:27:50 N, P and K kg ha-1), 25% N supplemented through farm yard manure or vermicompost+75% RDF with or without bio-fertilizers Azospirillum and Bacillus megaterium @ 5 kg ha-1 each in addition to control and replicated thrice. Each main treatment was divided into four subplots and the treatments of 100% RDF (20-22 N, P kg ha-1) and 75% RDF with or without Bradyrhizobium @ 500 g ha-1 (seed treatment) were imposed for hyacinth bean in rabi seasons and data was analyzed in split plot design. Integration of 100% RDF in conjunction with Bradyrhizobium seed treatment to hyacinth bean resulted in significantly higher water productivity, gross and net returns and maximum B:C during rabicompared to 100% RDF, 75% RDF with or without seed treatment. Integration of 75% RDF with 25% N through FYM along with biofertilizers to kharif baby corn showed significantly higher water productivity, gross and net returns of hyacinth bean during rabiover rest of the treatments of 100% RDF with or without biofertilizers and un-fertilized control but was at par with other organic treatments with or without biofertilizers due to residual effect.